Microporous film
Patent Information
- Application Number
- JP2026109242
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2017-11-03
- Filing Date
- 2026-06-22
- Publication Date
- 2026-10-16
Smart Images

Figure 2026169222000001_ABST
Abstract
Description
[Technical Field]
[0001] This application covers improved or novel porous membranes, separator membranes, battery separators, separator base films, lithium battery separators, batteries, lithium batteries or rechargeable lithium-ion batteries, and / or vehicles, devices, or products and / or related methods that incorporate them. According to at least one embodiment, this application or the present invention covers improved microporous membranes or films, and improved battery separators, separator base films, batteries, and devices that incorporate them. The microporous membranes or films described herein may be dry-process films manufactured by methods such as the Celgard® dry process. The membranes, films and products of the present invention exhibit improved properties with respect to at least certain conventional dry-process microporous films. The membranes or films of the present invention may preferably exhibit, among other properties, a reduced swelling rate when the film is wetted with an electrolyte. Swelling can lead to wrinkles in the film. Furthermore, the membrane or film of the present invention preferably has, among other properties, wrinkles and bagginess when the film is applied to the cell firing method used by battery manufacturers who use these films in batteries. It may show a reduction. [Background technology]
[0002] Recent trends in lithium battery technology, such as higher energy, higher voltage, faster charging speeds, and lower costs, add interesting and challenging requirements for battery separators. These trends may necessitate thinner, wider, higher-performance, and lower-cost separators. At least with respect to certain thinner or wider separators, it has been discovered that certain electrolyte solvents, such as dimethyl carbonate, diethyl carbonate, ethyl acetate, and others, can cause swelling and softening of certain microporous films used as lithium-ion battery separators in lithium-ion batteries or used in them. In particular, this phenomenon can occur in certain polyolefin-containing dry-process microporous films. When a dry-process microporous film is wetted with electrolyte in a battery, it can swell or expand. If the swelling is very high, TD wrinkles (or wrinkles running parallel to the TD direction of the film) may be observed. Wrinkling of the film leads to air incorporation and, being dry without electrolyte, can generate lithium precipitates.
[0003] From the aforementioned perspective, it is clear that a dry-process microporous film that does not swell and does not generate TD wrinkles, or that does not swell as much as certain conventional dry-process microporous films and does not generate many TD wrinkles, is desirable. Therefore, there is a need for such a film.
[0004] Many battery manufacturers include a firing process as part of their cell manufacturing method to remove moisture before electrolyte injection. The firing process may be described as 70-80°C for 24 hours and can cause sagging or drooping in certain microporous films. One problem observed in certain dry-process microporous films is that they can become "wavy and sagging" after the firing process. As described above, wrinkles lead to air intrusion, followed by lithium deposition. [Overview of the project] [Problems that the invention aims to solve]
[0005] From the aforementioned perspective, when subjecting batteries to the firing process used by many battery manufacturers, "wave" It is clear that a dry-process microporous film that does not exhibit "sagging" is desirable. Therefore, there is a need for such a film.
[0006] Furthermore, certain conventional dry-process microporous films tend to have issues with rebound elasticity after the prism-shaped jelly roll is pressed in the prism-shaped battery manufacturing method. As a result, the pressed jelly roll may swell and not fit into the battery can. In addition, certain dry-process films may be more elastic in the longitudinal direction, which can cause necking in the TD direction under high winding tension. These problems or challenges are specific to certain dry-process films or films. Improvements are highly desired to make dry-process films more competitive in cell manufacturing methods. For example, films with better rebound elasticity are desirable. Therefore, there is a need for such films. [Means for solving the problem]
[0007] According to at least selected embodiments, aspects, or purposes of the present invention or the present disclosure, novel or improved membranes, films, separator membranes, separator-based films, and / or battery separators are provided to address the above needs, problems, or challenges, and / or cells, batteries, devices, or products comprising such novel or improved membranes, films, separator membranes, and / or battery separators. According to at least specific embodiments, aspects, or purposes of the present invention or the present disclosure, novel or improved porous membranes, films, separator membranes, separator-based films, and / or battery separators are provided, and / or batteries, devices, vehicles, or products comprising such novel or improved porous membranes, films, separator membranes, and / or battery separators. According to at least specific embodiments, aspects, or purposes of the present invention or the present disclosure, novel or improved dry-process porous membranes, films, separator membranes, and / or battery separators are provided, and / or batteries, devices, vehicles, or products comprising such novel or improved dry-process porous membranes, films, separator membranes, and / or battery separators. According to at least selected embodiments, aspects, or purposes of the present invention or the present disclosure, a novel or improved dry process, polyolefin (polyethylene, polypropylene, or combinations, formulations, mixtures, copolymers, or block copolymers) microporous membrane, film, separator membrane, and / or battery separator can have reduced curling, sagging, drooping, firing wrinkles, and swelling in and / or the same in an electrolyte compared to conventional films, and / or batteries, lithium batteries, secondary lithium-ion batteries, devices, vehicles, and / or products comprising such a novel or improved dry process, polyolefin microporous membrane, film, separator membrane, and / or battery separator.
[0008] This specification describes microporous films that, according to at least certain embodiments, exhibit reduced swelling or no swelling when wetted with an electrolyte and / or do not sag or wrinkle when exposed to a firing process used by many battery manufacturers. According to at least some embodiments, the microporous films may exhibit other further desirable properties. In some preferred embodiments, the microporous films described herein are dry-process microporous films formed by a dry-stretching process such as the Celgard® dry-stretching process. A typical Celgard® dry-process (dry-stretched) film contains neither oil nor pore-forming agent nor nucleating agent.
[0009] In one embodiment, a microporous film is described herein, and in one preferred embodiment, the microporous film described herein is a dry-process microporous film formed by a dry-stretching process such as the Celgard® dry-stretching process. In some embodiments, the microporous film described herein has at least one of the following properties: when the film is fired unrestricted at 90°C for 1 hour, the film The film exhibits an unrestrained MD shrinkage rate of 2% or more; when the film is fired unrestrained at 105°C for 1 hour, it exhibits an unrestrained MD shrinkage rate of 2.5% or more; when measured using an MD-restrained expansion test, the film exhibits an MD-restrained expansion rate of 0.2% or less; when measured by a compression test, the film exhibits a rebound modulus or recovery rate of 5% or more; when measured by a compression test, the film exhibits a maximum compressibility of 18% or more; when measured by swelling in a diethyl carbonate (DEC) test, the film exhibits a swelling rate in DEC of 0.95% or less; when subjected to a puncture test, the film exhibits a round, non-slit-shaped opening; compared to conventional films, it exhibits a different electrolyte and / or similar properties. The following types may have reduced curl, reduced sagging, reduced drooping, reduced firing wrinkles, and reduced swelling; the three-layer battery separator includes PP / PE / PP layer thickness ratios of approximately 25 / 50 / 25 to approximately 35 / 30 / 35; the three-layer battery separator has a PP / PE / PP layer thickness ratio of approximately 30±3 / 40±6 / 30±3; film thickness less than 20 μm; film thickness less than 15 μm; film thickness less than 10 μm; film thickness less than 5 μm; film width of at least 50 mm; film width of at least 100 mm; film width of at least 150 mm; film width of at least 200 mm; film width of at least 250 mm; and the film lamellae have a thickness of 250 nm or less.
[0010] In some embodiments, the microporous films described herein exhibit unrestricted MD shrinkage rates of 2% or more, 3% or more, 4% or more, or 5% or more when the film is fired at 90°C for 1 hour under unrestricted conditions.
[0011] In some embodiments, the microporous films described herein exhibit unrestricted MD shrinkage rates of 2.5% or more, 3% or more, 6% or more, or 9% or more when the film is fired at 105°C for 1 hour under unrestricted conditions.
[0012] In some embodiments, the microporous films described herein exhibit a constrained MD expansion of 0.2% or less, about 0.1% or less, or about 0% as measured using a constrained MD expansion test.
[0013] In some embodiments, the microporous films described herein exhibit a rebound resilience or recovery rate of 5% or more as measured by a compression test.
[0014] In some embodiments, the microporous films described herein exhibit a maximum compressibility of 18% or more, 19% or more, or 20% or more as measured by a compression test.
[0015] In some embodiments, the microporous films described herein exhibit a swelling rate in DEC of 0.95% or less, 0.9% or less, 0.8% or less, 0.7% or less, or 0.6% or less as measured by a swelling test in DEC.
[0016] In some embodiments, the microporous films described herein exhibit openings that are round and not slit-shaped when subjected to a puncture test.
[0017] In some embodiments, the microporous film lamellae are no thicker than 250 nm.
[0018] In some embodiments, the microporous films described herein exhibit two or more, three or more, four or more, five or more, six or more, or all seven of the above properties.
[0019] In some embodiments, the microporous films described herein are three-layer battery separators or base films having a PP / PE / PP layer thickness ratio of about 25 / 50 / 25 to about 35 / 30 / 35. In more specific embodiments, the three-layer battery separator or the base film may have a preferred PP / PE / PP layer thickness ratio of about 30±3 / 40±6 / 30±3. It may be preferred that the PE layer is thicker than the PP layer or the thinnest PP layer.
[0020] In another embodiment, the battery separator comprises or essentially comprises one or more microporous films as described herein. The microporous films of the battery separator, or a plurality of microporous films, may be coated on one or both sides thereof. In some embodiments, the coating may be a ceramic coating.
[0021] In another embodiment, a battery comprising the above-mentioned battery separator is described. The battery may be a lithium-ion battery.
[0022] In another embodiment, a device comprising a battery separator or a battery as described herein is described. In some embodiments, the device may be an electric or hybrid vehicle, a laptop, a mobile phone, or the same. [Brief explanation of the drawing]
[0023] [Figure 1] This is a schematic diagram of single-sided coated and double-sided coated microporous films according to some embodiments described herein. [Figure 2] This is a schematic diagram of a lithium-ion battery. [Figure 3] This figure shows the dimensional change (%) versus applied force (N) for the present invention and comparative embodiments described herein. [Figure 4] The results of the puncture tests described herein for the embodiments of the present invention and comparative embodiments described herein are shown below. [Figure 5] This is a diagram of load versus displacement for embodiments of the present invention and comparative embodiments described herein. [Figure 6] This is a schematic diagram showing the structure of a microporous film according to some embodiments described herein. [Figure 7] This specification includes SEM measurements of microporous films of the present invention and comparison according to several embodiments. The thickness of the lamellae was measured. [Figure 8] This specification includes SEM measurements of microporous films of the present invention and comparison according to several embodiments described herein. The thickness of the lamellae was measured. [Figure 9] This specification includes SEM measurements of microporous films of the present invention and comparison according to several embodiments described herein. The thickness of the lamellae was measured. [Figure 10] This specification includes SEM measurements of microporous films of the present invention and comparison according to several embodiments described herein. The thickness of the lamellae was measured. [Figure 11] Figures 11(a) and 11(b) show comparative microporous films before (a) and after (b) cooling following 24-hour high-temperature firing as described herein. [Figure 12] Figures 12(a) and 12(b) show comparative (a) and the present invention (b) films after being subjected to the MD restraint expansion test described herein. [Figure 13] The MD stress-strain curves for the 12-14 micron and 16 micron three-layer materials of the present invention are shown, compared to the comparative 12-14 micron and 16 micron three-layer materials. [Figure 14] This includes, but is not limited to, cross-sectional SEM of certain low-swelling or low-rebound microporous films or base films of the present invention according to some specific embodiments herein, such as Examples 2a and 2b of the present invention. [Modes for carrying out the invention]
[0024] This application relates to improved or novel porous membranes, separator membranes, battery separators, separator base films, lithium battery separators, batteries, and lithium batteries. -or rechargeable lithium-ion batteries, and / or vehicles, devices, or products and / or related methods that incorporate them. According to at least one embodiment, the present application or the present invention relates to improved microporous membranes or films, and improved battery separators, separator base films, batteries, and devices comprising them. The microporous membranes or films described herein may be dry-process films manufactured by methods such as the Celgard® dry process. The membranes, films and products of the present invention exhibit improved properties with respect to at least certain conventional dry-process microporous films. The membranes or films of the present invention may preferably exhibit, among other properties, a reduced rate of swelling when the film is wetted with an electrolyte. Swelling can lead to wrinkles in the film. Furthermore, the membranes or films of the present invention may preferably exhibit, among other properties, a reduced wrinkle or sagging when the film is applied to a cell firing method used by battery manufacturers that use these films in these batteries.
[0025] Microporous films that can be used in battery separators are described herein. Among other properties, the microporous films exhibit reduced swelling when wetted with electrolyte and reduced or no sagging when exposed to the firing process used by battery manufacturers. The microporous films described herein also exhibit other advantageous properties.
[0026] The microporous films described herein are not limited to those described herein and may include any microporous films suitable for use in or as battery separators.
[0027] As used herein, the term “microporous” refers to a porous film having micropores. The average PP pore diameters of microporous films measured using an Aquapore porosimeter are 0.01–1 micron, 0.01–0.9 micron, 0.01–0.8 micron, 0.01–0.8 micron, 0.01–0.7 micron, 0.01–0.6 micron, 0.01–0.5 micron, 0.01–0.4 micron, 0.01–0.3 micron, 0.01–0.2 micron, 0.01–0.1 micron, 0.01–0.09 micron, 0.01–0.08 micron, 0.01–0.07 micron, 0.01–0.06 micron, 0.01–0.05 micron, 0.01–0.04 micron, 0.01–0.03 micron, or 0.01–0.02 micron. In some preferred embodiments, the pore size of the microporous film may be 0.03 to 0.04 microns, 0.04 to 0.05 microns, or 0.05 to 0.06 microns.
[0028] The aquapore porosimeter measures pore size using water intrusion technology. Its operating principle is similar to that of mercury intrusion porosimetry, but with lower toxicity and lower pressure. In a chamber, approximately 3 grams of membrane is first floated below the water surface. After degassing, the pressure is slowly increased to 2000 psi. The intrusion volume is measured against progressive pressure. The washburn formula is used to calculate pore size, pore size distribution, and surface area.
[0029] The shape of the pores in the microporous film is not limited to that, and may be slit-shaped, elliptical, circular, or substantially circular.
[0030] In some embodiments, the microporous films described herein can be manufactured using a dry process such as the Celgard® dry process. When used herein, the dry process generally involves extruding a thermoplastic resin into a parison (annular or flat), annealing the parison, stretching the annealed parison (uniaxially in the MD direction or biaxially in the MD and TD directions) to form micropores, and, if necessary, the microporous films. This describes a method for thermally curing pore films. Solvent extraction is not required, and plasticizers are not used to promote pore formation. Dry processes are well known; see, for example, Kesting, Synthetic Polymeric Membranes, John Wiley & Sons, New York, NY (1985), pp. 290-297 (incorporated herein by reference).
[0031] In some embodiments, the microporous films described herein can be manufactured using a wet process. As used herein, a wet process generally refers to a method of extruding a thermoplastic resin and a plasticizer (the plasticizer is then removed to form micropores) onto a flat sheet, cooling the flat sheet on a cold roll, stretching the cooled flat sheet, and extracting the plasticizer with a plasticizer solvent to form a microporous film. A wet process is based on a thermal phase inversion process (TIPS) or "phase inversion" process. Wet processes are well known; see, for example, Kesting, Synthetic Polymeric Membranes, John Wiley & Sons, New York, NY (1985), pp. 237–286 (incorporated herein by reference).
[0032] In some embodiments, the microporous films described herein are single-layer, double-layer, or multilayer (i.e., three or more layers) films. In some preferred embodiments, the microporous film is a three-layer film formed by laminating three separately formed single-layer films. The three-layer film may be formed by laminating after the pores have been formed by stretching the single-layer films, or the pores may be formed by stretching the single-layer films after the three-layer film has been formed. In some embodiments, the three-layer film has a structure of PP / PE / PP or PE / PP / PE, and the layers consist of or essentially consist of layers in which "PP" contains polypropylene and "PE" contains polyethylene. In some embodiments, the microporous film is a multilayer film formed by laminating three or more layers. In some multilayer embodiments, one or more layers to be laminated comprise two or more sublayers. Layers comprising two or more sublayers may be formed by co-extrusion. The layers and sublayers described herein may consist of or essentially consist of the same or different polymers. In some embodiments, the multilayer film may have the following structure (PP / PP / PP) / (PE / PE / PE) / (PP / PP / PP), comprising a triple sublayer consisting of or essentially consisting of (PP / PP / PP), where (PP / PP / PP) contains polypropylene. This layer may be formed by co-extrusion of three polypropylene-containing mixtures, which may be the same or different. The layer may have a triple sublayer consisting of or essentially consisting of (PE / PE / PE), where (PE / PE / PE) contains polyethylene. This layer may be formed by co-extrusion of three polyethylene-containing mixtures, which may be the same or different. Two (PP / PP / PP) layers are laminated with one (PE / PE / PE) layer to form the structure (PP / PP / PP) / (PE / PE / PE) / (PP / PP / PP). The microporous film may have the structure disclosed in International Publication No. 2017 / 083633 (which is incorporated herein by reference in its entirety).
[0033] The thickness of the microporous film may be 1 to 50 microns, 5 to 50 microns, 5 to 40 microns, 5 to 30 microns, 5 to 30 microns, 5 to 30 microns, 5 to 20 microns, or 5 to 10 microns. In some preferred embodiments, the microporous film has a thickness of 5 to 20 microns or 5 to 15 microns.
[0034] The JIS Gurley (seconds) of the microporous film is not limited to that and may be between 50 and 200 seconds. In some preferred embodiments, the microporous film may have a JIS Gurley (seconds) of less than 174 seconds, less than 170 seconds, less than 165 seconds, or less than 160 seconds. In some embodiments, the JIS Gurley (seconds) may be less than 200 seconds, less than 190 seconds, or It may be less than 180 seconds.
[0035] In some embodiments, the microporous film has a porosity of 20% to 60%. In some preferred embodiments, the porosity of the microporous film is 40% to 60%, 50% to 60%, 55% to 80%, 60% to 80%, 65% to 80%, 70% to 80%, or 75% to 80%.
[0036] In some embodiments, the microporous film is 75 g / m² 2 More than 80g / m 2 More than 85g / m 2 More than 90g / m 2 or more, or 95g / m² 2 The surface area is measured by the aquapore porosity method described above. In some embodiments, the surface area of the microporous film is 100 g / m². 2 As described above, it is acceptable for the value to be high.
[0037] In some embodiments, a microporous film or one or more layers or sublayers of a microporous film comprises or essentially comprises an extrudeable thermoplastic polymer. In some embodiments, the extrudeable thermoplastic polymer in one or more layers of the microporous polymer film comprises a polyolefin or a polyolefin compound. The polyolefin compound may include a mixture of two or more different polyolefins, such as polyethylene and polypropylene, or a mixture of two or more homogeneous polyolefins, where each polyolefin has different properties, such as an ultra-high molecular weight polyolefin and a low molecular weight or ultra-low molecular weight polyolefin, or a mixture of a polyolefin and another polymer or copolymer. In some embodiments, the microporous polymer film described herein may include an extrudeable polymer or polymer compound, such as a polyolefin or a polyolefin compound, and additives.
[0038] The polyolefins described herein, but not limited to, include: polyethylene, polypropylene, polybutylene, polymethylpentene, copolymers thereof, and formulations thereof. In some embodiments, the polyolefin may be ultra-low molecular weight, low molecular weight, intermediate molecular weight, high molecular weight, or ultra-high molecular weight polyolefins, such as intermediate or high molecular weight polyethylene (PE) or polypropylene (PP). For example, ultra-high molecular weight polyolefins may have a weight-average molecular weight of 450,000 (450k), 500k, 650k, 700k, 800k, 1 million, 2 million, 3 million, 4 million, 5 million, 6 million, or more than 6 million. High molecular weight polyolefins may have a molecular weight in the range of 250k to 450k, such as 250k to 400k, 250k to 350k, or 250k to 300k. Intermediate molecular weight polyolefins can have molecular weights in the range of 150k to 250k, such as 100k, 125k, 130k, 140k, 150-225k, 150k-200k, and 150k-200k. Low molecular weight polyolefins can have molecular weights in the range of 100k to 150k, such as 100k to 125k. Ultra-low molecular weight polyolefins can have molecular weights less than 100k. In some embodiments, higher molecular weight polyolefins can be used to improve the strength or other properties of the microporous multilayer films or batteries comprising them as described herein. In some embodiments, lower molecular weight polymers, such as intermediate, low, or ultra-low molecular weight polymers, may be beneficial. While we do not wish to be bound by any particular theory, for example, the crystallization behavior of lower molecular weight polyolefins can be considered to result in microporous multilayer films with smaller pores obtained from longitudinal (MD) or transverse (TD) stretching processes that form pores.
[0039] In some embodiments, the extrudeable thermoplastic polymer in one or more layers of the microporous polymer film includes a compound, mixture, or copolymer other than or in addition to a polyolefin polymer. One or more layers of the microporous polymer film include thermoplastic polymers such as polyacetal (or polyoxymethylene), polyamide, polyester, polysulfide, polyvinyl alcohol, polyvinyl ester, and polyvinylidene fluoride (PVDF), poly Polyvinylidene may include polyvinylidene fluoride (vinylidene-co-hexafluoropropylene) (PVDF:HFP), polytetrafluoroethylene (PTFE), polyethylene oxide (PEO), polyvinyl alcohol (PVA), and polyacrylonitrile (PAN). Examples of polyamides (nylon) include, but are not limited to, polyamide 6, polyamide 66, nylon 10,10, polyphthalamide (PPA), copolymers thereof, and formulations thereof. Examples of polyesters include, but are not limited to, polyterephthalate esters, polyterephthalate butyl, copolymers thereof, and formulations thereof. Examples of polysulfides include, but are not limited to, polyphenyl sulfides, copolymers thereof, and formulations thereof. Examples of polyvinyl alcohol include, but are not limited to, ethylene-vinyl alcohol, copolymers thereof, and formulations thereof. Examples of polyvinyl esters include, but are not limited to, polyvinyl acetate, ethylene-vinyl acetate, copolymers thereof, and formulations thereof. Examples of polyvinylidene include, but are not limited to, polyvinylidene fluoride (such as polyvinylidene chloride and polyvinylidene fluoride), copolymers thereof, and formulations thereof.
[0040] Additives to polymers or polymer formulations are not limited to the above and may include: lithium stearate, calcium stearate, PE beads, siloxanes, polysiloxanes, polymer treatment agents such as antioxidants, stabilizers, lubricants, processing aids, nucleating agents, colorants, antistatic agents, plasticizers, or fillers, cellulose nanofibers and the like.
[0041] In some embodiments, the microporous film has or exhibits at least 1, at least 2, at least 3, at least 4, at least 5, at least 6, or all 7 of the following properties: an unrestrained MD shrinkage of 2% or more when the film is baked at 90°C for 1 hour under unrestrained conditions; an unrestrained MD shrinkage of 2.5% or more when the film is baked at 105°C for 1 hour under unrestrained conditions; an MD restrained expansion of 0.2% or less as measured using the MD restrained expansion test; a rebound resilience or recovery rate of 5% or more as measured by a compression test; a maximum compressibility of 18% or more as measured by a compression test; a swelling rate in DEC of 0.95% or less as measured by the swelling test in DEC; when subjected to a puncture test, the film exhibits a round opening that is not slit-shaped; and the film lamella has a thickness of 250 nm or less.
[0042] The unrestrained MD shrinkage test may be performed at any temperature, but for the purpose of characterizing the microporous films described herein, the test is performed at 90°C and 105°C. For the unrestrained MD shrinkage test at 90°C, a sample of the microporous film is placed in a dryer under unrestrained conditions at 90°C for 1 hour. Unrestrained means that nothing holds the film in place at any location. To determine the percentage shrinkage of the film, the length of the film in the MD direction is measured before and after the sample is placed in the dryer under unrestrained conditions at 90°C for 1 hour. The shrinkage percentage % is obtained by the following formula (1): (│l i -l f │ / l i )×100 (1)
[0043] The microporous films according to the present invention described herein will obtain the following results when an unrestrained MD shrinkage test is performed at 90°C: the MD shrinkage rate is 2% or more, 3% or more, 4% or more, 5% or more, 6% or more, 7% or more, 8% or more, 9% or more, or 10% or more. In some preferred embodiments, the shrinkage rate is 2-5% when an unrestrained MD shrinkage test is performed at 90°C. Similar to the unrestrained MD shrinkage test at 90°C, the microporous film is placed in a dryer for 1 hour without restraint to perform an unrestrained MD shrinkage test at 105°C. For the unrestrained MD shrinkage test at 105°C, the dryer temperature is 105°C. The films according to the present invention described herein will have the following MD shrinkage rates when an unrestrained MD shrinkage test is performed at 105°C: 2.5% or more, 3% or more, 3.5% or more, 4% or more, 4.5% or more, 5% or more, 5% or more. MD shrinkage rates of 5% or more, 6% or more, 6.5% or more, 7% or more, 7.5% or more, 8% or more, 8.5% or more, or 9% or more. In some preferred embodiments, the MD shrinkage rates when performing an unrestrained MD shrinkage test at 105°C are 2.5% to 10%, 2.5% to 9%, 2.5% to 8%, 2.5% to 7%, 2.5% to 6%, 2.5% to 5%, 2.5% to 4%, and 2.5% to 3%. The unrestrained MD shrinkage tests at 90°C and 105°C are two tests that can be used to determine whether a given microporous film is a microporous film according to the present invention as described herein. The microporous films according to the present invention as described herein obtain the above results when measured by these tests.
[0044] In some embodiments, the microporous films according to the present invention as described herein yield the following results when measured by an MD-restrained expansion test: expansion of 0.2% or less, expansion of 0.1% or less, or expansion of about 0%. In some embodiments, the expansion may be negative; that is, the film may shrink slightly. For example, the expansion may be <0% to -5%, -0.1% to -5%, -0.1% to -4%, -0.1% to -3%, -0.1% to -2%, -0.1% to -1%, or -0.1% to -0.5%. The MD-restrained expansion test is another method for determining whether a given microporous film is the microporous film according to the present invention as described herein. The microporous films according to the present invention as described herein exhibit the above expansion when measured by an MD-restrained expansion test. The MD-restrained expansion test is performed to simulate the processing steps used by battery manufacturers according to the processing steps shown in Table 1 below.
[0045] [Table 1]
[0046] The MD-restrained expansion test is another method for determining the properties of microporous films according to the present invention as described herein. Microporous films that exhibit the above expansion (negative or positive expansion) are within the scope of the present invention as described herein, and films that do not exhibit the above expansion are not part of the present invention if they do not exhibit the other properties described herein.
[0047] In some embodiments, the microporous films described herein exhibit a rebound modulus or recovery rate of 5% or more, 6% or more, 7% or more, 8% or more, 9% or more, or 10% or more, as measured by compression testing. A rebound modulus or recovery rate of 20% or less may be exhibited by the microporous films described herein.
[0048] In some embodiments, the microporous films described herein exhibit a maximum compression ratio of 18% or more, 19% or more, 20% or more, 21% or more, 22% or more, 23% or more, 24% or more, 25% or more, 26% or more, 27% or more, 28% or more, 29% or more, or 30% or more. A maximum compression ratio of 40% or less is shown by the microporous films described herein. obtain.
[0049] Compression testing is yet another method for characterizing the microporous film according to the present invention as described herein and for determining whether a given microporous film is a film included in the present invention as described herein. If a given film exhibits the above-disclosed rebound modulus or recovery rate result or maximum compressibility result, the film is included in the present invention as described herein. If a given film does not exhibit the above-disclosed rebound modulus or recovery rate result or maximum compressibility result, the film is not included in the present invention as described herein.
[0050] A thermomechanical analyzer (TMA) equipped with a hemispherical probe is used for the compression test. The compressive force is increased to 0.5 N at a rate of 0.25 N / min. Then, the force is decreased to 0.01 N at the same rate. The compression percentage is calculated using the film thickness before and after the force is applied.
[0051] In some embodiments, the microporous films described herein exhibit a high auto-Young's modulus and a strain chord modulus of 2–5% in longitudinal tensile tests. The elongation before break is less than 40%. As a result, the films are highly resistant to longitudinal deformation under high cell winding tensions. The films are superior in battery manufacturing methods. This inherent characteristic is readily apparent as a steeper slope in stress and stress curves compared to comparative products.
[0052] Tensile properties are tested by stretching a 0.5-inch x 2-inch film sample using an Instron testing machine at a crosshead speed of 20 inches / minute. The maximum force and elongation at fracture are referred to as tensile strength and elongation, respectively. Stress-strain curves can be plotted using individual data points collected during the stretching process. Automatic and chord moduli can also be calculated using the data.
[0053] In some embodiments, the microporous films described herein exhibit a swelling rate in DEC of 0.95% or less, 0.90% or less, 0.85% or less, 0.80% or less, 0.75% or less, 0.70% or less, 0.65% or less, 0.60% or less, 0.55% or less, 0.50% or less, 0.45% or less, or 0.40% or less, as measured by a DEC swelling test. The DEC expansion rate test is another test for identifying microporous films encompassed by the present invention as disclosed herein. The microporous films according to the present invention as disclosed herein exhibit a DEC swelling rate value as measured by swelling in DEC, as described above. If a microporous film does not exhibit such a DEC swelling rate value, or does not exhibit any of the other properties of such a film, it is not a microporous film according to the present invention as disclosed herein.
[0054] In some embodiments, when a microporous film described herein is subjected to a puncture test, a circular, non-slit-shaped opening is formed in the film. The puncture test is another method for determining whether a given film is included in the invention as described herein. If the puncture test is performed on a microporous film and a slit-shaped opening is formed, the film is not included in the invention as described herein. Unless the film exhibits one of the other properties described herein, if a slit-shaped opening is formed when the film is subjected to a puncture test, the film is not included in the invention as described herein.
[0055] A puncture test is performed using an Instron compression tester. A 0.5 mm radius needle is attached to the crosshead of the tester at a crosshead speed of 25 mm / min, and the maximum force at the point of breakage of the membrane by the needle is recorded as the puncture strength. "Slit-like" is used to describe an opening whose length is approximately 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, or 10 times its height. The term "round" is used to describe an opening whose length is approximately 3 times, 2 times, 2.2 times, or 1 time its height. As shown in Figure 4, a round opening was formed when the microporous film of the present invention was subjected to a puncture test, and a slit-shaped opening was formed when the comparative microporous film was subjected to a puncture test.
[0056] In some embodiments, the microporous films described herein are dry-process microporous films, and the lamellae of the film are thinner than some other known conventional dry-process films. For example, the thickest lamellae cannot exceed 250 nm, 240 nm, 230 nm, 220 nm, 210 nm, 200 nm, 190 nm, 180 nm, 170 nm, or 160 nm. These are the maximum lamellar thickness values.
[0057] While we do not wish to be bound by any particular theory, it is thought that the thinner lamellae of the microporous films described herein may contribute not only to the puncture strength but also to the puncture openings. Lamellars are tightly packed crystalline regions, are more brittle, and tend to fracture first. In addition, the puncture openings are longer.
[0058] In some embodiments, the microporous films described herein may have a normalized puncture strength of 335 g / 16 microns or more. In some embodiments, the normalized puncture strength is 340 g / 16 microns or more, 350 g / 16 microns or more, 360 g / 16 microns or more, 370 g / 16 microns or more, 380 g / 16 microns or more, 390 g / 16 microns or more, 400 g / 16 microns or more, or 410 g / 16 microns or more. Normalizing the data for a specific thickness (16 microns) allows for the side-by-side consideration of thicker and thinner films. Normalization takes into account the fact that thicker films generally have higher puncture strengths than thinner films, especially when the films are otherwise similar or identical. For example, when two films are manufactured from similar or identical materials and / or methods. Normalization for 16 microns is performed using the following equation (a): (Sample puncture strength / Sample film thickness in microns) × 16 microns (a) Normalization for 20 microns is performed using the following equation (b): (Sample puncture strength / Sample thickness in microns) × 20 microns (b)
[0059] Battery separator In another embodiment, a battery separator comprising or essentially comprising at least one microporous membrane as disclosed herein is described. In some embodiments, at least one microporous membrane or microporous film (separator membrane, a separator base film to be coated) may be coated on one side or both sides to form a single-sided or double-sided coated battery separator. Single-sided coated (OSC) separators and double-sided coated (TSC) battery separators according to some embodiments herein are shown in Figure 1.
[0060] The coating layer may comprise, consist of, essentially consist of, and / or be formed from any of the coating compositions. For example, any of the coating compositions described in U.S. Patent No. 6,432,586, incorporated herein by reference, may be used. The coating layer may be, for example, wet, dry, crosslinked, non-crosslinked, PVD, CVD, or ALD, and may contain fillers or particles, or may not contain fillers or particles. The single-sided or double-sided coating may be replaced by a nonwoven material or other layer or material. The film or membrane of the present invention may or may not be coated, and may be single-layer, double-layer, triple-layer, or multi-layer.
[0061] In one embodiment, the coating layer may be the outermost coating layer of the separator, and may not have any other different coating layers formed on it, for example. The coating layer may have at least one other different coating layer thereon. For example, in some embodiments, a different polymer coating layer may be coated on or over a coating layer formed on at least one surface of the porous sublayer. In some embodiments, this different polymer coating layer may consist of, or essentially consist of, at least one of polyvinylidene fluoride (PVdF) or polycarbonate (PC).
[0062] In some embodiments, the coating layer is applied on top of one or more other coating layers already applied to at least one surface of the microporous film. For example, in some embodiments, these layers already applied to the microporous film are at least one thin, very thin, or ultrathin layer of an inorganic material, an organic material, a conductive material, a semiconducting material, a nonconductive material, a reactive material, or a mixture thereof. In some embodiments, these layers are metal or metal oxide-containing layers. In some preferred embodiments, the metal-containing layers and metal oxide-containing layers, for example, metal oxides of the metal used in the metal-containing layers, are formed on the porous sublayer, and then the coating layer comprising the coating composition described herein is formed. The total thickness of these already applied layers or layers may be less than 5 microns, less than 4 microns, less than 3 microns, less than 2 microns, less than 1 micron, less than 0.5 microns, less than 0.1 microns, or less than 0.05 microns.
[0063] In some embodiments, the thickness of the coating layer formed from the coating compositions described herein, for example, the coating compositions described in and incorporated herein by reference to U.S. Patent No. 8,432,586, is less than about 12 μm, sometimes less than 10 μm, sometimes less than 9 μm, sometimes less than 8 μm, sometimes less than 7 μm, and sometimes less than 5 μm. In at least certain selected embodiments, the coating layer is less than 4 μm, less than 2 μm, or less than 1 μm.
[0064] The coating method is not limited thereto, and the coating layer described herein may be applied to the porous sublayer as described herein by, for example, at least one of the following coating methods: extrusion coating, roll coating, gravure coating, printing, knife coating, air knife coating, spray coating, dip coating, or curtain coating. The coating method may be carried out at room temperature or high temperature.
[0065] The coating layer may be nonporous, nanoporous, microporous, mesoporous, or macroporous. The coating layer may have a JIS Gurley of 700 or less, sometimes 600 or less, 500 or less, 400 or less, 300 or less, 200 or less, or 100 or less. For nanoporous coating layers, the JIS Gurley may be 800 or more, 1,000 or more, 5,000 or more, or 10,000 or more (i.e., "infinite Gurley"). For nanoporous coating layers, the coating is nanoporous in the dry state, but especially when wetted with an electrolyte, the coating is a good ionic conductor.
[0066] Composite or device Provided in direct contact with these are any of the battery separators described herein and one or more electrodes, for example, an anode, a cathode, or a composite or device (cell, system, battery, capacitor, etc.) comprising an anode and a cathode. The type of electrodes is not limited thereto. For example, the electrodes may be suitable for use in lithium-ion secondary batteries. At least selected embodiments of the present invention are The present invention may be well suited for use with or in use with the latest high-energy, high-voltage, and / or high-coulomb-rate lithium batteries such as CE, UPS, or EV, EDV, ISS, or hybrid vehicle batteries, and / or for use with the latest high-energy, high-voltage, and / or high-charge / discharge or fast-charge / discharge electrodes, cathodes, and the like. At least certain embodiments of the present invention of thin (less than 12 μm, preferably less than 10 μm, more preferably less than 8 μm) and / or strong or robust dry-process films or separators may be well suited for use with or in use with the latest high-energy, high-voltage, and / or high-coulomb-rate lithium batteries (or capacitors), and / or for use with the latest high-energy, high-voltage, and / or high-charge / discharge or fast-charge / discharge electrodes, cathodes, and the like.
[0067] A lithium-ion battery according to at least some embodiments described herein is shown in Figure 2.
[0068] The anode material is not limited in this way. A suitable anode can have an energy capacity of 100 mAh / g or more, 200 mAh / g, 372 mAh / g, preferably ≥700 mAh / g, and most preferably ≥1000 mAh / g. The anode is composed of lithium metal foil or lithium alloy foil (e.g., lithium aluminum alloy), or a mixture of lithium metal and / or lithium alloy and materials such as carbon (e.g., coke, graphite), nickel, and copper. The anode is not produced from lithium-containing intercalation compounds or lithium-containing insertion compounds alone.
[0069] The cathode material is not limited in this way. A suitable cathode may be any cathode compatible with the anode and may be an intercalation compound, an insertion compound, or an electrochemically active polymer. Suitable intercalation materials include, for example, MoS2, FeS2, MnO2, TiS2, NbSe3, LiCoO2, LiNiO2, LiMn2O4, V6O 13Examples include V2O5 and CuCl2. Suitable polymers include, for example, polyacetylene, polypyrrole, polyaniline, and polythiopene.
[0070] The electrode material is not so limited. Generally, the electrode consists of, or essentially consists of, a solvent and a salt. Suitable solvents include at least one selected from EC, PC, DMC, EMC, DEC, and FEC. Salts are not so limited, and examples include lithium ion salts such as LiPF6. In some embodiments, additives such as at least one selected from vinylene carbonate, 1,3-propanesultone, 2-propynyl methanesulfonic acid, cyclohexylbenzene, t-amylbenzene, and adiponitrile may be added to the electrolyte material.
[0071] Any of the battery separators described herein above may be incorporated into any battery, lithium battery, CE, EDV, UPS, or ESS battery, or any vehicle, such as an e-vehicle, or device, such as a mobile phone or laptop, capacitor, wind system, solar system, or smart grid system, and / or similar devices that are fully or partially battery-powered or use batteries. [Examples]
[0072] The following examples were formed using a dry stretching process. Example 1 (12 micron PP / PE / PP three-layer): A 12 micron three-layer of PP / PE / PP in a 33% / 33% / 33% ratio according to the present invention. Example 2a (16 micron PP / PE / PP three-layer): 31% / 38% / 31% of the present invention PP / PE / PP 16 micron three-layer ratio Example 2b (16 micron PP / PE / PP trilayer): 16 micron trilayer of PP / PE / PP in a ratio of 31% / 38% / 31% according to the present invention. Example 3 (16 micron PP / PE / PP trilayer): 16 micron trilayer of PP / PE / PP in a ratio of 31% / 38% / 31% according to the present invention. Example 4 (Improved 14 μm trilayer): 13-14 micron trilayer of PP / PE / PP in a ratio of 33% / 33% / 33%. Example 5 (Improved 20 μm Trilayer): A 20-micron trilayer of PP / PE / PP in a 31% / 38% / 31% ratio according to the present invention. Comparative Example 1 (12 micron PP / PE / PP three-layer): A 12 micron three-layer of PP / PE / PP in a comparative ratio of 33% / 33% / 33%. Comparative Example 2 (16 micron PP / PE / PP three-layer): A 16 micron three-layer of PP / PE / PP with a comparative ratio of 33% / 33% / 33%. Comparative Example 3 (16 micron PP / PE / PP three-layer): A 16 micron single layer of PP for comparison. Comparative Example 4 (14 micron (PP / PP / PP) / (PP / PE / PP) / (PP / PP / PP)): A 14 micron three-layer structure with an overall ratio of 33% / 33% / 33% for comparison (PP / PP / PP) / (PP / PE / PP) / (PP / PP / PP)). Comparative Example 5 (14 μm three-layer): 14 micron three-layer construction of PP / PE / PP in a comparative ratio of 33% / 33% / 33%. Comparative Example 6 (20 μm three-layer): Low-Gurley 20-micron three-layer PP / PE / PP with a comparative ratio of 33% / 33% / 33%. Comparative example 7 (12μm three layers)
[0073] Some data from these examples are shown in Tables 2, 3, and 4 below.
[0074] [Table 2]
[0075] [Table 3]
[0076] [Table 4]
[0077] Compression test data A thermomechanical analyzer (TMA) equipped with a hemispherical probe is used for the compression test. The compressive force is increased to 0.5 N at a rate of 0.25 N / min. Then, the force is decreased to 0.01 N at the same rate. The compression percentage is calculated using the film thickness before and after the application of the force. The results are shown in Table 5 below.
[0078] [Table 5]
[0079] Puncture test data A puncture test is performed using an Instron compression testing machine. 25mm / A needle with a radius of 0.5 mm is attached to the crosshead of the testing machine using a minute crosshead speed, and the maximum force at the point of breakage of the film by the needle is recorded as the puncture strength. "Slit-shaped" is used to describe an opening whose length is approximately 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, or 10 times its height. "Round-shaped" is used to describe an opening whose length is approximately 3 times or less, 2 times, 2.2 times, or 1 time its height. As shown in Figure 4, a round-shaped opening was formed when the microporous film of the present invention (Example 4) was subjected to the puncture test, and a slit-shaped opening was formed when the comparative microporous film (Comparative Example 5) was subjected to the puncture test. For the example of the present invention, the opening has a height of 0.70 mm and a width or length of 1.57 mm. For the comparative example of the present invention, the opening has a height of 0.97 mm and a width or length of 10.98 mm.
[0080] Tensile test data Tensile properties were tested by stretching a 0.5-inch x 2-inch film sample in an Instron tester at a crosshead speed of 20 inches / min. The maximum force and elongation at fracture were referred to as tensile strength and elongation, respectively. Stress-strain curves could be plotted using individual data points collected during the stretching process. Automorphic and chord modulus could also be calculated using the data. Comparative examples and examples of 12-micron, 16-micron, and 20-micron samples were tested. The MD stress-strain curves are shown in Figure 13, and the calculated values for MD tensile strength, MD elongation before fracture, automorphic Young's modulus, and chord modulus are shown in Table 6 below.
[0081] [Table 6]
[0082] Therefore, the film of the present invention had a higher Young's modulus compared to a comparative product having the same thickness. For example, the 16-micron example of the present invention had a Young's modulus of 17,000 kgf / cm². 2 The 20-micron example of the present invention exhibited an extremely high auto-Young's modulus, while the 16-micron comparative example did not. 2 Super, 14,000kgf / cm 2 Over, or 15,000 kgf / cm² 2 The 12-micron example of the present invention exhibited an extremely high auto-Young's modulus, whereas the 20-micron comparative example did not. Furthermore, the 12-micron example of the present invention exhibited a high auto-Young's modulus of 13,000 kgf / cm². 2 Super, 14,000kgf / cm 2 Super, 15,000kgf / cm 2 Super, 16,000kgf / cm 2 Super, 17,000kgf / cm 2 Super, 18,000kgf / cm 2 Over, or 19,000 kgf / cm² 2The 12-micron comparative example had an ultra-high auto-Young's modulus, but the 12-micron comparative example did not. In some embodiments, the 12-micron sample had an MD pre-break elongation of less than 40%, less than 30%, or less than 20%. In some embodiments, the 16-micron sample had an MD pre-break elongation of less than 40% or less than 35%. In some embodiments, the 20-micron sample had an MD pre-break elongation of less than 45%, or less than 40%.
[0083] MD restraint expansion test An MD constrained expansion test is performed to simulate the processing steps used by battery manufacturers according to the processing steps shown in Table 1 above. The results of several comparative examples and embodiments of the present invention described herein are shown in Table 7 below.
[0084] [Table 7]
[0085] It was found that even MD expansion, and even 0.2% MD expansion, resulted in products with wavy sagging as shown in Figures 11(b) and 12(a). MD expansion of less than 0.2%, no MD expansion, or negative expansion (or contraction) are preferable. These products do not exhibit the "wavy sagging" seen in the comparative products.
[0086] Figures 11 and 12 visually illustrate these results. Figure 11(a) shows Comparative Example 6 before firing, and Figure 11(b) shows Comparative Example 6 after firing. The film is wrinkled and wavy. Figure 12(b) shows Example 5 of the present invention after firing. After firing, the example of the present invention is visibly wrinkle-free and not wavy.
[0087] DEC Medium Expansion Test The DEC expansion test is performed as follows: A membrane sample measuring 50 mm in length and 25 mm in width is cut along the longitudinal direction. Before immersion in diethyl carbonate for 1 hour (1 i ) after (l f Measure the length of the film using calipers. Calculate the swelling percentage using the following formula (3): (lf -l i ) / l i ×100 (3)
[0088] Examples 1, 2a, 2b, 3, 4, and 5, and Comparative Examples 2, 3, 6, and 7 were tested, and the results are shown in Table 3 above and Table 8 below. It was found that the examples of the present invention showed less swelling than the comparative examples.
[0089] [Table 8]
[0090] SEM A comparative SEM image of the 16 μm three-layer structure of the present invention was taken at 20,000x magnification and is shown in Figure 7. Compared to the lamellar thickness of Example 2a of the present invention, which was 195 nm, the thickest lamellar of Comparative Example 2 was 390 nm. The average lamellar thickness of Comparative Example 2 was approximately 158 nm, while the average thickness of Example 2a of the present invention was 132 nm.
[0091] A comparative SEM image of the 20 μm three-layer structure of the present invention was taken at 20,000x magnification and is shown in Figure 8. Compared to the lamellar thickness of Example 5 of the present invention, which was 170 nm, the thickest lamellar of Comparative Example 6 was 301 nm.
[0092] SEM images of the comparative example and Example 1 of the present invention, both 2 μm three layers, were taken at 20,000x magnification and are shown in Figure 9. Compared to the lamellar thickness of Example 1 of the present invention, which was 153 nm, the thickest lamellar of Comparative Example 1 was 195 nm.
[0093] According to at least selected embodiments, aspects, or purposes of the present invention or the present disclosure, novel or improved membranes, films, separator membranes, separator-based films, and / or battery separators are provided to address the above needs, problems, or challenges, and / or cells, batteries, devices, or products comprising such novel or improved membranes, films, separator membranes, and / or battery separators. According to at least specific embodiments, aspects, or purposes of the present invention or the present disclosure, novel or improved porous membranes, films, separator membranes, separator-based films, and / or battery separators are provided, and / or batteries, devices, vehicles, or products comprising such novel or improved porous membranes, films, separator membranes, and / or battery separators. According to at least specific embodiments, aspects, or purposes of the present invention or the present disclosure, novel or improved dry-process porous membranes, films, separator membranes, and / or battery separators are provided, and / or batteries, devices, vehicles, or products comprising such novel or improved dry-process porous membranes, films, separator membranes, and / or battery separators. According to at least selected embodiments, aspects, or purposes of the present invention or the present disclosure, a novel or improved dry process, polyolefin (polyethylene, polypropylene, or combinations, formulations, mixtures, copolymers, or block copolymers) microporous membrane, film, separator membrane, and / or battery separator can have reduced curling, sagging, drooping, firing wrinkles, and swelling in and / or the same in an electrolyte compared to conventional films, and / or batteries, lithium batteries, secondary lithium-ion batteries, devices, vehicles, and / or products comprising such a novel or improved dry process, polyolefin microporous membrane, film, separator membrane, and / or battery separator.
[0094] This specification describes microporous films that, according to at least certain embodiments, exhibit reduced swelling or no swelling when wetted with an electrolyte and / or do not sag or wrinkle when exposed to a firing process used by many battery manufacturers. According to at least some embodiments, the microporous films may exhibit other further desirable properties. In some preferred embodiments, the microporous films described herein are dry-process microporous films formed by a dry-stretching process such as the Celgard® dry-stretching process. A typical Celgard® dry-process (dry-stretched) film contains neither oil nor pore-forming agent nor nucleating agent.
[0095] Disclosed herein is a microporous film having at least one of the following characteristics: an unrestrained MD shrinkage rate of 2% or more when the film is fired unrestrained at 90°C for 1 hour; an unrestrained MD shrinkage rate of 2.5% or more when the film is fired unrestrained at 105°C for 1 hour; an MD restrained expansion rate of 0.2% or less when measured using an MD restrained expansion test; a rebound modulus or recovery rate of 5% or more when measured by a compression test; a maximum compressibility of 18% or more when measured by a compression test; and a swelling rate in DEC of 0.95% or less when measured by a DEC swelling test; the film exhibits circular, non-slit-shaped openings when subjected to a puncture test; the film lamellae have a thickness of 250 nm or less; a normalized puncture strength of more than 350 g / 16 microns; and a higher modulus of elasticity and less than 40% elongation before break in the longitudinal direction. Also disclosed herein are a battery separator, battery, or device comprising at least one microporous film as described herein.
[0096] The embodiments described herein can be more readily understood by referring to the following detailed specification and examples. However, the elements, apparatus and methods described herein are not limited to the specific embodiments shown in the detailed specification and examples. It should be recognized that these embodiments are merely illustrative of the principles of this disclosure. Any modifications and adaptations would be readily apparent to those skilled in the art without departing from the intent and scope of this disclosure.
[0097] In addition, all scopes disclosed herein are understood to encompass any and all subscopes contained therein. For example, the defined scope "1.0 to 10.0" should be considered to include any and all subscopes that begin with a minimum value of 1.0 or greater and end with a maximum value of 10.0 or less, such as 1.0 to 5.3, or 4.7 to 10.0, or 3.6 to 7.9.
[0098] The entire scope disclosed herein shall be deemed to include the endpoints of the scope unless expressly otherwise specified. For example, the scopes “5-10 (between 5 and 10),” “5-10 (from 5 to 10),” or “5-10 (5-10)” should generally be deemed to include the endpoints 5 and 10.
[0099] Furthermore, the phrase "up to" is used in relation to amount or quantity, and the amount is understood to be at least a detectable amount or quantity. For example, a material indicated as "up to" a specific amount may exist in an amount ranging from a detectable amount to a specific amount or less.
[0100] Unless otherwise explicitly stated, all molecular weight values described herein are weight-average molecular weights.
Claims
1. A microporous film with the following characteristics: When the aforementioned film is fired at 90°C for 1 hour under unrestrained conditions, an unrestrained MD shrinkage rate of 2% or more is obtained; When the aforementioned film is fired at 105°C for 1 hour without restraint, the unrestrained MD shrinkage rate is 2.5% or more; When measuring using the MD constrained expansion test, the MD constrained expansion should be 0.2% or less; When measured by compression testing, the rebound modulus or recovery rate must be 5% or higher; When measured by compression testing, the maximum compressibility is 18% or more; In the case of measurement by the DEC swelling test, the swelling rate in DEC is 0.95% or less. Having at least one of; When subjected to a puncture test, the aforementioned film exhibits a circular, non-slit-shaped opening; The lamellae of the film have a thickness of 250 nm or less; It has a normalized puncture strength of over 350 g / 16 microns; It has a higher modulus of elasticity in the longitudinal direction and an elongation before break of less than 40%. Microporous film.
2. The microporous film according to claim 1, having at least two of the above-mentioned properties.
3. The microporous film according to claim 1, having at least three of the above characteristics.
4. The microporous film according to claim 1, having at least four of the above characteristics.
5. The microporous film according to claim 1, having at least five of the above characteristics.
6. The microporous film according to claim 1, having at least six of the above characteristics.
7. The microporous film according to claim 1, having at least seven of the above characteristics.
8. The microporous film according to claim 1, having at least eight of the above characteristics.
9. The microporous film according to claim 1, wherein when the film is fired at 105°C for 1 hour under unrestrained conditions, the film has an unrestrained MD shrinkage rate of 2.5% or more.
10. The microporous film according to claim 1, wherein when the film is fired at 105°C for 1 hour under unrestrained conditions, the film has an unrestrained MD shrinkage rate of ≥3%.
11. The microporous film according to claim 1, wherein when the film is fired at 105°C for 1 hour under unrestrained conditions, the film has an unrestrained MD shrinkage rate of ≥6%.
12. The microporous film according to claim 1, wherein when the film is fired at 105°C for 1 hour under unrestrained conditions, the film has an unrestrained MD shrinkage rate of ≥9%.
13. The microporous film according to claim 1, wherein when the film is fired at 90°C for 1 hour under unrestrained conditions, the film has an unrestrained MD shrinkage rate of 2% or more.
14. The microporous film according to claim 1, wherein when the film is fired at 90°C for 1 hour under unrestrained conditions, the film has an unrestrained MD shrinkage rate of ≥3%.
15. The microporous film according to claim 1, wherein when the film is fired at 90°C for 1 hour under unrestrained conditions, the film has an unrestrained MD shrinkage rate of ≥4%.
16. The microporous film according to claim 1, wherein when the film is fired at 90°C for 1 hour under unrestrained conditions, the film has an unrestrained MD shrinkage rate of ≥ 5%.
17. The microporous film according to claim 1, wherein the film has MD-restrained expansion of 0.2% or less.
18. The microporous film according to claim 1, wherein the film has MD-restrained expansion of 0.1% or less.
19. The microporous film according to claim 1, wherein the film has MD-constrained expansion of about 0.
20. The microporous film according to claim 1, wherein the film exhibits a rebound modulus or recovery rate of 5% or more when measured by a compression test.
21. The microporous film according to claim 1, wherein the film exhibits a maximum compressibility of 18% or more when measured by a compression test.
22. The microporous film according to claim 1, wherein the film exhibits a maximum compressibility of 19% or more when measured by a compression test.
23. The microporous film according to claim 1, wherein the film exhibits a maximum compressibility of 20% or more when measured by a compression test.
24. The microporous film according to claim 1, wherein the film exhibits a swelling rate of 0.95% or less in DEC when measured by the DEC swelling test.
25. The microporous film according to claim 1, wherein the film exhibits a swelling rate in DEC of 0.8% or less when measured by the DEC swelling test.
26. The microporous film according to claim 1, wherein the film exhibits a swelling rate in DEC of 0.7% or less when measured by the DEC swelling test.
27. The microporous film according to claim 1, wherein the film exhibits a swelling rate of 0.6% or less in DEC when measured by the DEC swelling test.
28. The microporous film according to claim 1, wherein the film exhibits a swelling rate of 0.5% or less in DEC when measured by the DEC swelling test.
29. The microporous film according to claim 1, wherein the film exhibits a swelling rate in DEC of less than 0.4% when measured by the DEC swelling test.
30. The microporous film according to claim 1, wherein the film exhibits circular, non-slit-shaped openings when subjected to a puncture test.
31. The microporous film according to claim 1, wherein the film has a normalized puncture strength of 350 g / 16 microns.
32. The microporous film according to claim 1, wherein the film has a normalized puncture strength of 360 g / 16 microns.
33. The microporous film according to claim 1, wherein the film has a normalized puncture strength of 370 g / 16 microns.
34. The microporous film according to claim 1, wherein the film has a normalized puncture strength of 380 g / 16 microns.
35. The microporous film according to claim 1, wherein the film has a normalized puncture strength of 390 g / 16 microns.
36. The microporous film according to claim 1, wherein the film has a normalized puncture strength of 400 g / 16 microns.
37. The microporous film according to claim 1, wherein the lamellae of the film have a thickness of 250 nm or less.
38. The microporous film according to claim 1, wherein the film has a higher modulus of elasticity and a lower pre-break elongation of less than 40% in the longitudinal direction.
39. A battery separator comprising the microporous film described in claim 1.
40. The battery separator according to claim 39, wherein at least one surface of the microporous film has a coating provided thereon.
41. The battery separator according to claim 39, wherein both sides of the microporous film have a coating provided thereon.
42. The battery separator according to claim 40 or 41, wherein at least one of the coatings is a ceramic coating.
43. A secondary battery comprising a battery separator according to any one of claims 39 to 42.
44. The secondary battery according to claim 43, wherein the secondary battery comprises an electrolyte solvent selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethylmethyl carbonate (EMC), diethyl carbonate (DEC), and monofluoroethylene carbonate (FEC).
45. A device comprising the secondary battery described in claim 44.
46. A three-layer battery separator containing PP / PE / PP layer thickness ratios ranging from approximately 25 / 50 / 25 to approximately 35 / 30 / 35.
47. The three-layer battery separator according to claim 46, wherein the PP / PE / PP layer thickness ratio is approximately 30±3 / 40±6 / 30±3.
48. Novel or improved membranes, films, base films, separator membranes, separators, or battery separators as described or claimed herein.
49. A method for manufacturing a battery using the novel or improved membrane, film, base film, separator membrane, separator, or battery separator described or claimed herein.
50. Novel or improved thin, wide, and / or high charge capacity (greater than 2 coulombs) films, base films, separator films, separators, or battery separators as described or claimed herein.